A novel technique for optimizing the placement of phasor measurement units (PMUs) using complex network theory - Zeeshan Nazir Ahmad (NUST201463526MCES64114F); Dr Syed Muhammad Raza Kazmi (USPCAS-E, NUST, Islamabad, 2017)
TH-77
Keywords: MS-ESE Thesis MS Thesis